Green kiwifruit (lat. Actinidia deliciosa var. Hayward) and maintenance of normal defecation: evaluation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 - EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA); Dominique Turck; Jacqueline Castenmiller; Stefaan De Henauw; Karen Ildico Hirsch‐Ernst; John Kearney; Helle Katrine Knutsen; Alexandre Maciuk; Inge Mangelsdorf; Harry J McArdle; Androniki Naska; Carmen Pelaez; et al. (EFSA Journal, 2021)
Abstract Following an application from Zespri International Limited, submitted for authorisation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of Belgium, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to green kiwifruit (lat. Actinidia deliciosa var. Hayward) and maintenance of normal defecation. The scope of the application was proposed to fall under a health claim based on newly developed scientific evidence. The food proposed by the applicant as the subject of the health claim is green kiwifruit. The Panel considers that green kiwifruit (Actinidia deliciosa var. Hayward) is sufficiently characterised. The claimed effect proposed by the applicant is ‘maintenance of normal defecation’. Maintenance of normal defecation is a beneficial physiological effect provided that it does not result in diarrhoea. All human intervention studies submitted had different limitations and could not be used on their own for the scientific substantiation of the claim. However, the results of six pertinent human intervention studies are consistent with respect to an effect of consuming daily between two and four green kiwifruits var. Hayward on an increase in stool frequency. Two out of four studies in which a validated instrument was used to assess stool consistency showed an effect also on stool consistency. There is evidence for a plausible mechanism by which kiwifruit could exert an effect on normal defecation. The consumption of kiwifruit in the studies did not result in diarrhoea. A cause and effect relationship has been established between the consumption of green kiwifruit (Actinidia deliciosa var. Hayward) and maintenance of normal defecation. The following wordings reflect the scientific evidence: ‘consumption of kiwifruit contributes to the maintenance of normal defecation’. In order to obtain the claimed effect, two large green kiwifruits (i.e. around 200 g of kiwi flesh) should be consumed.